Neurotoxic snakebites at a primary healthcare center in Nepal: an experience of a PAHS graduate (Journal of Patan Academy of Health Sciences, 2020)
Nepal has one of the highest snakebite fatalities in South Asia. Most bites occur in rural areas where there is a lack of both adequate facilities for treatment and transport. Despite several limitations, prompt access and focus on supportive care are the major strengths of peripheral healthcare centers. Here we present the management of two cases of neurotoxic snakebites. Timely intervention can save lives in case of snakebites; hence establishment of snakebite treatment centers in the periphery can mitigate the problem of delay in care. Patan Academy of Health Sciences can contribute by training medical graduates in snakebite management.